Optimizing interfacial energetics for conjugated polyelectrolyte electron injection layers in high efficiency and fast responding polymer light emitting diodes - Hamilton,I; Suh,M; Bailey,J; Bradley,DDC; Kim,J-S (ACS Applied Materials and Interfaces, 2022)
Modification of the π-conjugated backbone structure of conjugated polyelectrolytes (CPEs) for use as electron injection layers (EILs) in polymer light emitting diodes (PLEDs) has previously brought conflicted results in the literature in terms of device efficiency and turn-on response time. Herein, we determine the energetics at the CPE and the light emitting polymer (LEP) interface as a key factor for PLED device performance. By varying the conjugated backbone structure of both the LEP and CPE, we control the nature of the CPE/LEP interface in terms of optical energy gap offset, interfacial energy level offset, and location of the electron–hole recombination zone. We use a wide gap CPE with a shallow LUMO (F8im-Br) and one with a smaller gap and deeper LUMO (F8imBT-Br), in combination with three different LEPs. We find that the formation of a type II heterojunction at the CPE/LEP interfaces causes interfacial luminance quenching, which is responsible for poor efficiency in PLED devices. The effect is exacerbated with increased energy level offset from ionic rearrangement and hole accumulation occurring near the CPE/LEP interface. However, a deep CPE LUMO is found to be beneficial for fast current and luminance turn-on times of devices. This work provides important CPE molecular design rules for EIL use, offering progress toward a universal PLED-compatible CPE that can simultaneously deliver high efficiency and fast response times. In particular, engineering the LUMO position to be deep enough for fast device turn-on while avoiding the creation of a large energy level offset at the CPE/LEP interface is shown to be highly desirable.